504 Assessment of the Clinical Benefits of Pitolisant on Excessive Daytime Sleepiness and Cataplexy in Adults With Narcolepsy. (3rd May 2021) - Meskill, Gerard; Davis, Craig; Zarycranski, Donna; Doliba, Markiyan; Schwartz, Jean-Charles; Dayno, Jeffrey
Abstract: Introduction: When evaluating results of randomized, placebo-controlled trials, the clinical impact of a treatment can be assessed using number needed to treat (NNT; number of patients that need to be treated to achieve a specific outcome for one person) and effect size (magnitude of drug–placebo difference on outcome measures). Lower NNTs indicate a more robust effect; NNT <10 is generally considered to represent a meaningful between-treatment difference. This analysis evaluated NNTs and effect sizes for pitolisant in the treatment of excessive daytime sleepiness (EDS) and cataplexy, using data from 7- or 8-week, randomized, placebo-controlled studies. Methods: Patients in both studies experienced EDS at study baseline (Epworth Sleepiness Scale [ESS] score ≥14 in HARMONY-1 and ≥12 in HARMONY-CTP); patients in HARMONY-CTP also experienced ≥3 cataplexy attacks/week. Pitolisant was titrated over a 3-week period to a maximum potential dose of 35.6 mg/day, after which the dose remained stable. End-of-treatment assessments occurred at Week 8 in HARMONY-1 and Week 7 in HARMONY-CTP. Treatment response was defined for EDS based on ESS score reduction (≥3-point decrease from baseline or final score ≤10) and for cataplexy as ≥50% reduction from baseline to stable-dose period in the weekly rate of cataplexy (WRC). NNTs were calculated as the inverse of the drug–placebo difference in response rates. Effect sizes for change from baseline in mean ESS score and WRC were calculated using Cohens' d. Missing values were imputed using a last-observation-carried-forward approach. Results: Treatment response for EDS was observed in HARMONY-1 (pitolisant, n=31; placebo, n=30) in 67.7% of pitolisant-treated versus 43.3% of placebo-treated patients (NNT=5) and in HARMONY-CTP (pitolisant, n=54, placebo, n=51) in 68.6% versus 34.0% of patients, respectively (NNT=3). In HARMONY-CTP, treatment response for cataplexy was observed in 66.7% of pitolisant-treated patients versus 25.5% of placebo-treated patients (NNT=3). Effect sizes were 0.61 (HARMONY-1) and 0.86 (HARMONY-CTP) based on ESS change scores, and 0.86 (HARMONY-CTP) based on change in WRC. Conclusion: The low NNTs and large effect sizes observed in this analysis provide further evidence that pitolisant produces meaningful clinical benefits in the treatment of EDS and cataplexy in adults with narcolepsy. Support (if any): Bioprojet Pharma and Harmony Biosciences, LLC.